2016
DOI: 10.1177/2158244016663717
|View full text |Cite
|
Sign up to set email alerts
|

Progressive and Conservative “Freedom” Through the Lens of FOX and MSNBC

Abstract: This research examines the framing of health care and immigration policy debates by high profile cable television (TV) pundits on FOX News and MSNBC. The study uses an interpretive framework to apply Lakoff’s (2006) conceptualization of “freedom” as a contested idea within political discourse in the United States. Qualitative content analysis was used to examine 322 TV transcripts. Findings indicate that in both the health care debates of 2009 and immigration debates of 2010, conservative and progressive cable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…2 These differences in public views of the BLM movement depending on one's political orientation may be caused by differences in how news media with different political stances represent the movement. Previous studies have found that news media present different political realities in accordance with their ideological leanings (e.g., Aday et al, 2005;McDonald & Morgaine, 2016). For example, the political leanings of news media were associated with how news media represent racial injustice and racism (el-Nawawy & Elmasry, 2021).…”
Section: Partisan Bias Of News Outlets and The Representation Of The ...mentioning
confidence: 99%
“…2 These differences in public views of the BLM movement depending on one's political orientation may be caused by differences in how news media with different political stances represent the movement. Previous studies have found that news media present different political realities in accordance with their ideological leanings (e.g., Aday et al, 2005;McDonald & Morgaine, 2016). For example, the political leanings of news media were associated with how news media represent racial injustice and racism (el-Nawawy & Elmasry, 2021).…”
Section: Partisan Bias Of News Outlets and The Representation Of The ...mentioning
confidence: 99%